2017
DOI: 10.3791/54997
|View full text |Cite
|
Sign up to set email alerts
|

<em>In Vivo</em> Investigation of Antimicrobial Blue Light Therapy for Multidrug-resistant <em>Acinetobacter baumannii</em> Burn Infections Using Bioluminescence Imaging

Abstract: Burn infections continue to be an important cause of morbidity and mortality. The increasing emergence of multidrug-resistant (MDR) bacteria has led to the frequent failure of traditional antibiotic treatments. Alternative therapeutics are urgently needed to tackle MDR bacteria. An innovative non-antibiotic approach, antimicrobial blue light (aBL), has shown promising effectiveness against MDR infections. The mechanism of action of aBL is not yet well understood. It is commonly hypothesized that naturally occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
4
13
0
2
Order By: Relevance
“…Previous studies both in our laboratory and other research groups demonstrated that aBL effectively eradicated a panel of clinical pathogenic microbes, including Acinetobacter baumannii , Pseudomonas aeruginosa , Candida albicans , MRSA and Neisseria gonorrhea (22‐23,25,29‐30,33‐40). In the present study, we showed that aBL was equally effective in inactivating M. catarrhalis , an otopathogen, both in suspensions and in biofilms.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies both in our laboratory and other research groups demonstrated that aBL effectively eradicated a panel of clinical pathogenic microbes, including Acinetobacter baumannii , Pseudomonas aeruginosa , Candida albicans , MRSA and Neisseria gonorrhea (22‐23,25,29‐30,33‐40). In the present study, we showed that aBL was equally effective in inactivating M. catarrhalis , an otopathogen, both in suspensions and in biofilms.…”
Section: Discussionmentioning
confidence: 87%
“…The photochemical effect of blue light irradiation at 1.0 mW/cm 2 for 60 min (with an energy dose of 3.6 J/cm 2 ) without CHPB added achieved nearly a 9.2% inactivation rate for A. baumanni, and the rate for blue light irradiation at 2.0 mW/cm 2 for 120 min reached approximately 68.4% (at an energy dose of 14.4 J/cm 2 ) in Figure 5 . It has been reported that the utility of antimicrobial therapy for multidrug-resistant A. baumanni infection in a mouse-burned model suggests that blue light significantly reduced the bacterial burden in mouse burns by endogenous porphyrins within A. baumannii cells [ 48 , 49 ]. Endogenous intracellular porphyrins are similar to photosensitizers, in that they can be excited by blue light and, in turn, create ROS, causing cell death [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…For basic research on bacterial infections, the use of luminescent bacterial strains and the detection by bioluminescence imaging are widely used tools 22,56,57 . However, as this procedure requires transiently transformed bacteria and in the present study we aimed to apply a complex biological sample (CS) for contamination, bioluminescence imaging was no option.…”
Section: Discussionmentioning
confidence: 99%